The Relationship between Exposure Level of in Passive Smoking with Maximum Oxygen Uptake (VO2max) among Adolescents Aged 19-24 Years Old - Safitri, Ines Aprilia; ., Arif Suryawan; ., Bagus Wicaksono (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Background: The prevalence of passive smokers tends to increase along with theÂ prevalence of active smokers. Most of university students are passive smokers, who get the exposure in home and social environment. The exposure of cigarette smoking can harm human health, especially for cardiovascular and respiratory system. VO2max is the best parameter to measure human cardiorespiratory ability. This research aimed to analyze the relationship between exposure level in passive smokers with maximum oxygen uptake (VO2max) in adolescents aged 19-24 years old. Methods: This was an observational analytic study with cross-sectional design. The research was conducted in Mei 2015. Using the consecutive sampling, we selected 72 passive smokers aged 19-24 years old, Sebelas Maret University students, who classified into medium and high exposure level. The data were collected by using questionnaire and interview. VO2max was measure with Mc Ardle Step Test method. The data was analyzed with Chi Square test. Results: The results showed that passive smokers were mostly women. Most of sample had good VO2max, which were 37.5% in medium exposure level and 23.6% in high exposure level. The sample with average VO2max were 8.3% in medium exposure level and 15.3% in high exposure level. The sample with low VO2max were 11.1% in medium exposure level and 4.2 % in high exposure level. Chi Square test result showed p = 0.095. Conclusions: There is no statistically significant relationship between exposure level in passive smokers with maximum oxygen uptake (VO2max) on adolescents aged 19-24 years old. Keywords: Passive Smokers, VO2max.Â